ANALISIS SEMIOTIKA PESAN DAKWAH DALAM FILMAIR MATA DI UJUNG SAJADAHPERSPEKTIF CHARLESS SANDER PIERCE - Rukanda Sastra Gunawan; Arif Ramdan Sulaiman; Nella Novianti; Fauziah Azzahra (Lembaga Sepercenter, 2026)
This study aims to determine the method of delivering da'wah in the film “Air Mata di Ujung Sajadah” (Tears at the End of the Prayer Mat) from the perspective of Charles Sanders Peirce using the symbols of sign, object, and interpretant. In addition, this study also aims to determine the message of da'wah contained in the film Air Mata di Ujung Sajadah. This research was conducted from April to August 2025 using a qualitative approach and semiotic analysis to observe and examine the film in order to identify the symbols present and identify the da'wah messages by determining the categories of aqidah messages, akhlak messages, and syariah messages. Based on the results, the study interpreted and concluded that the film “Air Mata di Ujung Sajadah” has various ways of conveying religious messages, namely 35 ways with sharia and morals, with moral messages as the most dominant category. Meanwhile, other message categories still exist but with less frequency.